Cannibalism on planktonic eggs by a non-filter feeding fish, Micropogonias furnieri (Sciaenidae) - Acha, Eduardo Marcelo (2002)
Cannibalism by fishes on planktonic eggs is typical of filter-feeding marine planktivores, i.e. fishes that have the ability for filtering large volumes of water and concentrate small food particles. We report an unusual case of cannibalism on planktonic eggs by adults of the non-filter feeding fish Micropogonias furnieri, which are opportunistic bottom-feeding carnivores that prey mainly on polychaetes, molluscs and crustaceans. Spawning of M. furnieri takes place in the innermost part of the Río de la Plata estuary, near the upstream edge of a salinity wedge. Strong haloclines retain planktonic eggs in a bottom salty layer, thin enough to generate spatial coexistence of the planktonic eggs and the bottom associated adults. Moreover, eggs remain sufficiently concentrated as to be sucked in by fish lacking filtering apparatus. It has been stated that cannibalism appears to be genetically based but controlled or induced by different environmental cues. Our case, however, shows that environmental influence on cannibalism is not restricted to a signal that triggers the cannibalistic behavior: oceanographic processes may also act generating specific scenarios that promote and perhaps regulate the occurrence of cannibalism.